TANGGAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum.L) VARIETAS LEMBAH PALU PADA BERBAGAI UKURAN UMBI DAN DOSIS PUPUK KALIUM - Nurdiana Entaunayah; Henry Barus; Adrianton Adrianton (Universitas Tadulako, 2015)
The purposes of the research was to determine the effects of tuber sizes andpotassium fertilizerrates on growth and yield of Lembah Palu shallot varieties. This research was conducted in Simoro village, Gumbasa Sub District in Regency of Sigi. Laboratory work for yield component observations were done in Seed Technology Laboratory of Agriculture Faculty, Tadulako University. This research was conducted from June to August 2013. A randomized block design was used for designingthe research within which two factors were applied namely tuber size (U) and rates of potassium (K). The tuber size consist of small tuber (U1= 1.7-2.3gtuber-1) and large tuber (U2= 2.4-3.0 gtuber-1). The potassium fertilizer (K2O) consist of four rates; 100 kgha-1, 150 kgha-1, 200 kgha-1, 250 kgha-1. The research treatments was replicated three times. The results research showed that tuber dimension significantly affected all growth parameters except plant height and all yield parameters. The large tuber grew better than small tuber. While K rates showed significant effect for all growth parameters except shoot numbers and all yield parameters, except tuber number per plants. The rates of K above 100kgha-1 showed greater yield 6.41 tonha-1 than the low rate 100 kgha-1 only 5.66 tonha-1. There was a significant interaction effect between tuber size and rates of K fertilizer for all parameters growth, except leaf number and shoot number, and all parameter yields except tuber diameter. The potassium fertilizerinfluence the growth, yield of and corm quality. The potassium fertilizer function is to strengthen the crop vigor along with forming and enlarging tuber diameter. Key words : K dosage, Shallot varieties lembah palu, Tuber size.